PECULIARITIES OF OCCUPATIONAL ILLNESS FORMATION IN ROSTOV REGION - T. Y. Bykovskaya; T. E. Pictushanskaya; I. N. Pictushanskaya; A. I. Shabalkin (Acta Biomedica Scientifica)
The data base on occupational illness in Rostov region in 2002—2011 has been formed. Branch and occupational structure and. dynamics of relative indices of occupational illness with the economics branch consideration have been analysed. The tendency of reducing occupational illness indices in Rostov region has been revealed, it being caused by incomplete revealing the patients with occupational illness. Coal mining industry, in which the high level of occupational illness is caused by the extremely unfavourable conditions of labor, is an exception. It is necessary to increase the efficiency of periodical medical examinations, especially for agricultural workers, in order to reveal the real level of occupational illness.